Chemical probing of the homopurine.homopyrimidine tract in supercoiled DNA at single-nucleotide resolution - Vojtísková, M; Mirkin, S; Lyamichev, V; Voloshin, O; Frank-Kamenetskii, M; Palecek, E (FEBS letters, 1988)
Local structure of the homopurine.homopyrimidine tract in a supercoiled plasmid pEJ4 was studied using chemical probes at single-nucleotide resolution. The conformation of the homopyrimidine strand was probed by osmium tetroxide, pyridine (Os,py) while that of the homopurine strand was tested by diethyl pyrocarbonate (DEPC), i.e. by probes reacting preferentially with single-stranded DNA. At weakly acidic pH values, a strong Os,py attack on three nucleotides at the centre of the (dC-dT)16 block and a weaker attack on two nucleotides at the end of the block were observed. DEPC modified adenines in the 5'-half of the homopurine strand. Os,py modification at the centre of the block corresponded to the loop of the hairpin formed by the homopyrimidine tract, while DEPC modification corresponded to the unstructured half of the homopurine strand in the model of protonated triplex H form of DNA.
Keywords: Molecular Sequence Data; restrikční enzymy; nukleotidy - mapování; geny; Genes; Pyrimidines; pyrimidiny; DNA Restriction Enzymes; histony; Base Sequence; sekvence nukleotidů; Histones; zvířata; superhelikální DNA; DNA, Superhelical; Plasmids; Purines; Sea Urchins; puriny; plazmidy; ježovky; Nucleotide Mapping; molekulární sekvence - údaje; Animals